The city and the chaos : the presentation of urban open spaces in dystopian films: a apresentação dos espaços urbanos abertos em filmes distópicos - Dettmann, Beatriz (Geografares, 2021)
In the digital media it is announced the growth in the production of dystopian works, with emphasis on the audiovisual media. This type of work has as its fundamental characteristic the creation of a place, the dystopia, which is identified by the great magnitude of its social conflicts. This work aims to study the places produced by dystopian films. To this end, we selected for the analysis the urban open spaces of the dystopias, where the problems of the city tend to be highlighted. The method of this work consists of the study of a sample of films, based on the morphologies of its cities. The different spatial configurations found in the films give us evidence of the existence of some aspects of politics in these places are repeated.